Partnerships, urban policies and institutional change: A comparative analysis of area-based initiatives and the new localism(s) in England and Germany. - Hohmann, Rene Peter (My University, 2011)
In the face of continuing problems of urban decline and a long history of area based policies for urban regeneration, an increasing local policy activism can be observed in a number of European countries since the mid-1990s. These New Localism(s) embrace new ways in which the delivery of both public services and urban regeneration are managed. The formulation and implementation of area-based initiatives (ABIS) for deprived urban areas, such as The "New Deal for Communities (NDC)" in Bristol (England) and the "Social City Programme (SCP)" in Duisburg (Germany), are examples of this trend. By decentralising management responsibilities from local authorities to development partnerships at the neighbourhood level, ABIS can be seen as test-beds for new forms of urban governance and new public service delivery mechanisms that seek to foster an active participation of residents and Voluntary Sector Organisations (VSOs). This comparative research compares and evaluates the impacts of these New Localism(s) on local development strategies and processes for deprived urban areas in these two localities. It identifies similarities and differences of transformative pressures exerting on local state spaces across Europe. Revealing the multifaceted nature of contingent outcomes of these governance experiments, it suggests that researching New Localism(s) in different institutional settings provide a rich field of study for future research agendas on comparative urbanism across Europe. Using a neo-institutional analytical framework and mixed methods approach it addresses attention to the specific situations in which new local policy partnerships operate, acknowledges the contested, ambivalent nature of institutional change and questions analytical attempts that predict universal, institutional outcomes of these governance experiments.
Keywords: Stadtentwicklungsplanung; Stadterneuerung; Partizipation; Städtebauförderung; Stadtteil; Problemraum; Stadtsoziologie; Stadtquartier; Wohnbevölkerung; Bewohnerbeteiligung; Nachbarschaft; Bevölkerungsstruktur; Kommunalpolitik; Soziodemographie; Soziale Stadt; Benachteiligter Stadtteil; Urban Governance; Neo-Institutionalismus